Elimination of support mechanism in additive manufacturing through substrate tilting. Issue 7 (8th October 2018) - Kapil, Sajan; Joshi, Prathamesh; Kulkarni, Pravin Milind; Negi, Seema; Kumar, Ranjeet; Karunakaran, K.P.
Abstract : Purpose: The support structures of sacrificial material are built in deposition-based additive manufacturing (AM), which are later removed either by breaking or dissolving. Such a sacrificial material is not feasible in metal AM. The purpose of this study is to find a suitable method for eliminating the need of support mechanism. In this work, the authors use the tilting of the substrate to alleviate the need for the support mechanism altogether. Design/methodology/approach: As in the traditional AM, the object is grown in horizontal layers. However, wherever undercuts are encountered, the substrate is tilted appropriately to capture the droplets. Such a tilt involves two rotary axes invariably. To conform to the slice geometry, these two tilts are accompanied by the three linear movements. Thus, the object with undercuts is grown in planar layers using five-axis deposition without any support structure. Each pair of the corresponding top and bottom contours of any slice defines a ruled surface. The axis of the deposition head will be aligned with the rules of this surface. Findings: The need for the support mechanism was eliminated using five-axis deposition. This was experimentally demonstrated by building an aluminum impeller using a metal inert gas cladding head. Research limitations/implications: In the proposed methodology, the objects with an abrupt change in the geometry are not possible to realize. Originality/value: This manuscript proposed a novel method of eliminating the support mechanism through continuous five-axis deposition.